Desempenho da técnica de citometria de fluxo, no diagnóstico precoce da toxoplasmose congênita - Tonini, Aline de Castro Zacche (2014)
The routine diagnosis of pos-natal congenital toxoplasmosis is based on the detection of IgM and/or IgA anti-T. gondii antibodies in neonates sera. However, in a significant number of infected newborns these antibodies are not detected, hindering the early diagnosis of the disease. Therefore, in this study it was evaluated the performance of the detection of anti-T. gondii antibodies by flow cytometry in the sorological diagnosis of early pos-natal congenital toxoplasmosis., Eight eight sera samples of children with congenital infection by T.gondii (TOXO) and 19 sera samples of uninfected children were evaluated. The sensitivity of the test was 47.6% for IgM, 72.6% for IgA, and 75% for IgG, with 100% of specificity for all tests. As to the IgG subclasses, the sensitivity was 73.9% for IgG1, 60.2% for IgG2, and 83% for IgG3 with 100% of specificity for all tests. The sensitivity of IgG4 was superior to the aformentioned subclasses reaching 94.7%, although achieved a poor specificity of 4.6%. The IgG avidity when employed to segregate TOXO and NI groups presented a great performance, with 97% of sensitivity and 93% of specificity. It was also done a comparative analysis of the presence of IgG and IgG3 in children of TOXO and NI groups with their respective mothers. Our results showed that the children with congenital toxoplasmosis presented an average reactivity of these antibodies equivalent to their respective mothers, which suggests that they are producing antibodies in response to T.gondii infection. In contrast, uninfected children presented a lower average reactivity of those antibodies in comparison to their respective mothers. In addition, our study proposed an algorithm for the diagnosis of congenital toxoplasmosis using IgM test performed by conventional methods available in routine clinical laboratories as the initial approach followed by the search for IgG3 and IgG avidity using flow cytometry, reaching a final performance of 98% of sensitivity and 93% of specificity. Data analysis showed the applicability of flow cytometry for the detection of IgG3 antibodies and IgG anti-T. gondii avidity as a complementary tool for the early diagnosis of congenital toxoplasmosis.